ANALISIS BIAYA DAN TENAGA KERJA PADA BEBERAPA KILANG PENGGERGAJIAN DI SUMATERA SELATAN - Sylviani Sylviani; Akub J Abdurachman (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
The result of research on several sawmills in South Sumatera showed that average level of manager productivity is 7.563 Cu.m/man/annum, administration productivity is 3.220 Cu.m/man/annum, tecnician productivity is 74 Cu.m/man/annum. Average labor requirements are 9 men/1.000 Cu.m of the design capacity and 10 men/1.000 Cu.m of raw material.Cost of production of sawntimber showed an average of Rp 184.808,-/Cu.m, in which the processing cost alone ranked high up to an average of 83 %, marketing cost 10 %, and general cost 7 %. Profit generated of each mill per annum ranged from Rp 891.060.692,- to Rp 3.165.279.700,- or equivalent to an average of Rp 80.053 per Cu.m.